Although the question does not state, I will assume the purpose is to factor -x2 - 11x + 26
Find factors of 26: 1 and 26; 2 and 13. The goal is to use these factors to arrive at the number in the middle, 11. Which means the 1 and 26 will not work.
Because the first coefficient is negative, when you separate your equation, one x must be positive, one must be negative, as below.
ANS: (-x - 13)(x - 2)
-x2 - 11x + 26 = -(x2 + 11x - 26) = -(x2 - 2x + 13x - 26) = -[ x(x - 2) + 13(x - 2) ] = -(x + 13)(x - 2) = (x + 13)(2 - x)
572 Because 2x11=22 and 13x2=26 and 22x26=572.
-1(x-13)(x+2). APEX Answer
Do you mean x2+11x-26 if so then it is (x-2)(x+13) when factored
Divide all terms by -1 so: x2-11x-26 = (x+2)(x-13) when factored
-x2 - 11x + 26 = -(x2 + 11x - 26) = -(x2 - 2x + 13x - 26) = -[ x(x - 2) + 13(x - 2) ] = -(x + 13)(x - 2) = (x + 13)(2 - x)
-x2 - 11x + 26= -x2 - 13x + 2x + 26= (2x - x2) + (26 - 13x)= x(2 - x) + 13(2 - x)= (2 - x)(x + 13)
572 Because 2x11=22 and 13x2=26 and 22x26=572.
-1(x-13)(x+2). APEX Answer
Do you mean x2+11x-26 if so then it is (x-2)(x+13) when factored
x^3 - 121x
X2 -11x +10=(x - 1 )(x - 10)
Divide all terms by -1 so: x2-11x-26 = (x+2)(x-13) when factored
(x + 13)(2 - x)
If you meant to write -x2 - 11x + 26, that factors to -(x - 2)(x + 13)
x^2 + 11x + 6 has no rational zeros.
x2+11x+11 = 7x+9 x2+11x-7x+11-9 = 0 x2+4x+2 = 0 The above quadratic equation can be solved by using the quadratic equation formula and it will have two solutions.